Penguatan Pemahaman Kekerasan Berbasis Gender Online (KBGO) Bagi Guru-Guru SMA Muhammadiyah 3 Jakarta Selatan - Sri Mustika; Tellys Corliana; Andys Tiara; Yulmaida Amir (Universitas Muhammadiyah Surakarta, 2023)
On the basis of the rapid increase in the use of digital access, especially for adolescents as the majority of internet users and concurrently with the KBGO case,